Numerical and experimental application of the automated slump test for yield stress evaluation of mineralogical and polymeric materials - Pereira, João Batista [UNESP]; Sáo, Yuri Taglieri [UNESP]; de Freitas Maciel, Geraldo [UNESP] (Springer Nature, 2022)
This work presents reliable empirical correlations of slump and spread measurements with yield stress of different materials based on the automated slump test methodology (capable of monitoring the transient regime of the slump test and minimizing operational errors — better control and reproducibility of tests). Measures of the final samples, such as slump and spread, are then correlated to yield stress, assessed through a rotational rheometer. The reliability of this methodology is corroborated by numerical simulations of the slump test using Ansys Fluent 14.5. A series of sensitivity tests was made and numerical results showed the importance of including the mold and its lifting velocity in the simulations. Such experimental control and good agreement of numerical-experimental results allowed the definition of well-validated empirical models for yield stress estimation. Correlations with an elevated coefficient of determination (R2> 0.90) were obtained using a new dimensionless parameter relating slump and spread measurements. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Automated slump test; Empirical models; Non-Newtonian fluids; Numerical simulation; Yield stress